Mitigating Underinvestment through Accounting Conservatism: A Comparative Study of Family and Non-Family Firms in Taiwan - LIN, I-CHENG; WEI, WAN-LING; YAO, CHI-YANG; LUO, YAN-YAN (International Journal of Business and Social Science Research, 2024)
This study examines the role of accounting conservatism in mitigating underinvestment due to internal cash flow volatility in Taiwan-listed and OTC companies from 2013 to 2022, comparing family and non-family firms. Utilizing regression analysis, we assess how accounting conservatism influences investment decisions under varying conditions of cash flow stability. Our findings reveal that accounting conservatism significantly alleviates underinvestment across all sampled firms, particularly in family firms where its impact becomes pronounced under high cash flow volatility conditions. In contrast, conservatism does not significantly affect investment decisions in stable cash flow scenarios. Additionally, the study finds that accounting conservatism can reduce capital costs under high cash flow volatility, thereby promoting investment. These insights provide a new understanding of the function of accounting conservatism across different firm types and offer practical guidance for financial decision-making.